Analisis Peningkatan Kasus HIV/AIDS Di Kota Medan: Faktor-Faktor Yang Mempengaruhi Dan Implikasi Untuk Pencegahan Dan Edukasi - Suci Frisnoiry; Julisa Ayu Lestari; Cut Rania Andini; Putri Br Tarigan (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to analyze the increase in HIV/AIDS cases in Medan City with a focus on influencing factors and implications for prevention and education. The research method used is library study, by collecting and analyzing data from literature, documents and related reports from various sources, including scientific journals, books and official reports from health and government organizations. The results of the analysis show that factors such as risky behavior, low levels of public awareness, lack of access to health services, and social stigma have a significant role in increasing HIV/AIDS cases. The implication of these findings is the need to increase efforts in prevention and education, with a focus on increasing awareness, reducing stigma, increasing accessibility of health services, and strengthening collaboration between various stakeholders in addressing this problem. This research makes an important contribution to understanding the dynamics of HIV/AIDS epidemiology in Medan City and provides a basis for developing more effective intervention strategies.